A case report of hepatic subcapsular hematoma: Newborn with an autoimmune hemolytic condition - Yunxin Li; Aijie Wang; Ranran Huang; Guowei Zhang (Clinical Case Reports)
Key Clinical Message We report a case of hepatic subcapsular hematoma in a newborn baby detected with an autoimmune hemolytic condition due to ABO incompatibility. Magnetic resonance imaging could be helpful in differentiating hepatic subcapsular hematoma from other abdominal masses.